Plantanone D, a new rare methyl-flavonoid from the flowers of Hosta plantaginea with anti-inflammatory and antioxidant activities. Issue 22 (18th November 2021) - Yang, Li; Zhu, Yuye; He, Zhongwei; Zhang, Tingfang; Xiao, Zhixi; Xu, Ruoling; He, Junwei
Abstract: Flowers of Hosta plantaginea have been used for the treatment of inflammation-related diseases in traditional Chinese medicine with limited scientific validation. In the present work, we reported one new rare methyl-flavonoid, plantanone D (1 ) and one known compound 4-hydroxybenzoic acid (2 ) from the flowers of H. plantaginea . Their structures were elucidated on the basis of chemical and spectral evidence, as well as by comparison with literature data. To the best of our knowledge, the methyl-flavonoid skeleton have not been reported from any species in Liliaceae family, compound 2 was isolated from the genus Hosta for the first time. The anti-inflammatory activities against cyclooxygenases (COX-1 and COX-2) and antioxidant activities in vitro results revealed that 1 exhibited significant COX-1 inhibition and moderate COX-2 inhibition compared to the reference celecoxib. Additionally, 1 displayed significant antioxidant activity compared to the positive control L-ascorbic acid. Graphical Abstract: